2019
DOI: 10.1371/journal.pone.0214932
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and social identity in the Mid Upper Paleolithic: New personal ornaments from Poiana Cireșului (Piatra Neamț, Romania)

Abstract: Most of the Paleolithic art and ornaments discovered in Romania come from the site of Poiana Cireșului. Four Paleolithic layers have been studied at this site—the oldest one belongs to the Early Gravettian period between 30 ka and 31 ka BP. The ornaments discovered in this layer include perforated shells from three species of mollusks: freshwater Lithoglyphus naticoide and Lithoglyphus apertus as well as Homalopoma sanguineum (an exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…The ornaments discovered in the third Gravettian layer (26/27 ka uncal. BP) at Poiana Cireșului are completely different from those found in the first level and include an association of perforated shells not found in any other Gravettian settlement (Nițu et al, 2019). The perforated shells come from three species of molluscs: freshwater Lithoglyphus naticoide and Lithoglyphus apertus as well as Homalopoma sanguineum (an exclusively Mediterranean species).…”
Section: Perforated Shellsmentioning
confidence: 67%
See 4 more Smart Citations
“…The ornaments discovered in the third Gravettian layer (26/27 ka uncal. BP) at Poiana Cireșului are completely different from those found in the first level and include an association of perforated shells not found in any other Gravettian settlement (Nițu et al, 2019). The perforated shells come from three species of molluscs: freshwater Lithoglyphus naticoide and Lithoglyphus apertus as well as Homalopoma sanguineum (an exclusively Mediterranean species).…”
Section: Perforated Shellsmentioning
confidence: 67%
“…Ornaments made of shells of the (Taborin 1993a, b;d'Errico, Jardón-Giner, Soler-Mayor 1993;d'Errico et al 2005;Avezuela 2010) and after the experiments we have made (Cârciumaru, Țuțuianu-Cârciumaru 2012 ;Nițu et al 2019), it has been concluded that all the Lithoglyphus shells of Poiana Cireșului were perforated from the inside by pressure exerted with an antler or hardwood sharp point inserted through the aperture after the shell had been fastened to a fixed blank. The position of the orifice on the last whorl of the shell was chosen so as not to endanger the resistance of that specimen, on the one hand, and to ensure an efficient hanging, so that the centre of gravity should determine a relatively similar position for all items and, finally yet importantly, answer the aesthetic requirements intended.…”
Section: Figurementioning
confidence: 95%
See 3 more Smart Citations